Handbuch Sprache im Recht - Felder, Ekkehard; Vogel, Friedemann (Handbücher Sprachwissen, 2017)
"The Handbook of Language in Law documents the textual and communicative processes of setting standards in the law. Its focus is on the legal explication of meaning, as examined from the perspectives of the courts, the legislature, the executive, and legal science. For the first time, it provides linguists, legal scholars, and social scientists with an introductory compendium on the theory, empiricism, and methodology of legal linguistics"--